URBAN DEVELOPMENT AND ENVIRONMENTAL ISSUES: A CASE STUDY OF THE OCCUPATION TO THE BANKS OF THE AMAZON RIVER IN THE NEIGHBORHOOD OF ARAXÁ, MACAPÁ, AMAPÁ BRAZIL - Maurício-da-Costa, Jodival (2016)
This article focuses on investigating how the urban space of Araxá is configured -specifically on the border of the neighborhood and the residents’ relationship with this environment. The job aims at studying if the current proposals for intervention involving the study area and the families who reside there are in line with the desire of the local population. For this purpose, the study area was identified in regards to urban infrastructure; interviews were made to local residents to identify the socio-economic issues, as well as to understand the relationship of the inhabitants of the area with the location, and to know if they are satisfied with the current proposal of intervention intended by the State. Before identifying the area, the urbanization process of towns and major transformations in space Amapá were analyzed in order to understand the emergence of unequal spaces, from the urban development of the cities, through bibliographical revision. It was concluded that the current proposals are disjoined and far from the expectations of those involved in the areas of intervention.